2010
DOI: 10.4278/ajhp.090313-lit-101
|View full text |Cite
|
Sign up to set email alerts
|

Health Coaching to Improve Healthy Lifestyle Behaviors: An Integrative Review

Abstract: Health coaching studies with well-specified methodologies and more rigorous designs are needed to strengthen findings; however, this behavioral change intervention suggests promise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
247
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 267 publications
(269 citation statements)
references
References 18 publications
10
247
0
4
Order By: Relevance
“…34 Indeed, as the trajectory of peer-reviewed articles on this approach rapidly increases, continued variability in definitions of health coaching precludes the ability to perform rigorous reviews or meta-analyses. This variability also ensures continued confusion over the coaching approach and confounds the skills needed by the rapidly growing number of professionals providing health and wellness coaching.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…34 Indeed, as the trajectory of peer-reviewed articles on this approach rapidly increases, continued variability in definitions of health coaching precludes the ability to perform rigorous reviews or meta-analyses. This variability also ensures continued confusion over the coaching approach and confounds the skills needed by the rapidly growing number of professionals providing health and wellness coaching.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…The most recent prior review of the effectiveness of health coaching reviewed only 15 articles and concluded that the body of literature as a whole was inconclusive due to theoretical and methodological issues. 34 It will be of great interest to revisit the issue of whether health coaching will be consistently effective at promoting health change now that we have a much larger body of work to review (284 articles), and if health coaching is defined, as by this consensus, as patient-centered, incorporating patient-determined goals, self-discovery processes, accountability, and content information, in the context of an ongoing helping relationship. This unified assessment will be fundamental to establishing the merit of this approach to helping people…”
Section: Areas For Further Investigationmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies demonstrated the efficacy of motivational interviewing as a positive psychology approach to promote goal achievement (Butterworth, Linden, McClay, & Leo, 2006) and define it as a strategy focused on collaboration around a central goal in order to coach a client toward lifestyle change (Olsen & Nesbitt, 2010).…”
Section: Coachingmentioning
confidence: 99%